2017
DOI: 10.12688/f1000research.10085.1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting blood transfusion and predictors of outcome in cardiac surgery patients: a concise perspective

Abstract: In the United States, cardiac surgery-related blood transfusion rates reached new highs in 2010, with 34% of patients receiving blood products. Patients undergoing both complex (coronary artery bypass grafting [CABG] plus valve repair or replacement) and non-complex (isolated CABG) cardiac surgeries are likely to have comorbidities such as anemia. Furthermore, the majority of patients undergoing isolated CABG have a history of myocardial infarction. These characteristics may increase the risk of complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…2017)[ 12 ] with a proven reduction in both costs and complications. There have however been contrarian thoughts from the specialty of CS highlighting the role of anemia in aggravating renal injury[ 13 ] and transfusion in improving more global outcome,[ 14 ] our study could not demonstrate any association between blood component use and AKI-CS.…”
Section: Discussioncontrasting
confidence: 67%
“…2017)[ 12 ] with a proven reduction in both costs and complications. There have however been contrarian thoughts from the specialty of CS highlighting the role of anemia in aggravating renal injury[ 13 ] and transfusion in improving more global outcome,[ 14 ] our study could not demonstrate any association between blood component use and AKI-CS.…”
Section: Discussioncontrasting
confidence: 67%
“…The burden of disease in Indigenous Australians is more than twice that of nonā€Indigenous Australians and chronic disease, such as cardiovascular and chronic kidney disease, play a major role in this disparity . Patients who have had cardiac surgery and chronic kidney disease have increased blood transfusion requirements that may adversely affect their clinical outcomes, especially since their blood group antigens are poorly characterized. Our study has shown the value of massively parallel sequence data toward elucidating complete blood group antigen profiles for the Indigenous Australian population for comparison with other population groups.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive blood loss during cardiac surgery is associated with an increased incidence of blood transfusion, reoperation, prolonged hospital stay and death. [1][2][3][4] Excessive blood loss may be due to surgical factors alone, but may be compounded by impaired coagulation if plasma coagulation factors fall below critical levels. 4 This is more likely if cardiopulmonary bypass (CPB) is used, due to the associated haemodilution.…”
Section: Introductionmentioning
confidence: 99%